Factor XII-Dependent Fibrinolysis: A Double Function of Plasma Kallikrein and the Occurrence of a Previously Undescribed Factor XII- and Kallikrein-Dependent Plasminogen Proactivator - Kluft, C; Trumpi-Kalshoven, M M; Jie, A F H; Veldhuyzen-Stolk, E C (Thrombosis and Haemostasis, 1979)
Fibrinolytic studies in euglobulin fractions of Fletcher trait plasma (deficient in prekallikrein) revealed reduced activities as compared to normal plasma. A quantitative assay for total plasminogen activator plus proactivator in plasma showed that the amount in Fletcher trait patients is about half of normal (normal = ± 100 blood activator units [BAU]/ ml). Plasma kallikrein partially purified in a high and low molecular weight form exerted plasminogen activator activity amounting to 10–15 BAU/ml plasma. So, the absence of kallikrein in the deficient plasma can not fully account for the reduction in activator activity. Additions of kallikrein preparations or normal plasma fractions resulted in additional activator activity in Fletcher trait plasma which was assessed at 30–40 BAU/ml. This activity was assumed to originate from a previously undescribed plasminogen proactivator whose activation is kallikrein- and factor XH-dependent.Fractionation experiments demonstrated the presence of two major activities and a minor activity caused by kallikrein in normal plasma.It is concluded that plasma kallikrein has two functions in the generation of factor XII- dependent fibrinolytic activity: one as a direct plasminogen activator and another as a factor in the activation of a major factor XH-dependent plasminogen proactivator.